Aproximación a las recomendaciones de la Misión del Mercado de Capitales y su impacto en los portafolios de los Fondos de Pensiones (2021)
This article analyzes the implications of applying the recommendations given in the Capital Market Mission (Misión del Mercado de Capitales, MMC by its acronym in Spanish) on the pension funds' investment regulation in Colombia. I solve a portfolio choice problem with strategic interactions to estimate the pension funds' optimal investment policies under two scenarios. The first one simulates the current regulation, while the second one is a proposal of MMC's recommendations. These investment policies are compared with the affiliate's optimal investment policy to define which scenario is the most convenient. On the one hand, under the current regulatory scenario, the affiliates risk profiling is not representative and there is a risk that the pension fund's investment policy moves away from the affiliate's optimal investment policy when relative performance concerns increase. On the other hand, under the MMC scenario proposal, the affiliates' risk profiling is more precise and varied. The pension fund's investment policy moves forward to the affiliate's optimal investment policy and is stable under changes in another pension fund's investment decisions.